Reconquer the land: resistance and organization of peasants at the end of the corporate-military dictatorship - Braga Brito, Ricardo (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2021)
At the end of 1979, the São José da Boa Morte farm was occupied in Cachoeiras de Macacu (RJ), by peasants organized with their Rural Union and Comissão Pastoral da Terra. The farm had already been the scene of occupations in 1961 and 1963, and its occupation was expressive once again at a time of redemocratization in Brazil. Through interviews with leaders and peasants and analysis of union, repression and journalistic documents, we sought to reconstruct the moment of the occupation and its meanings for the group of actors who occupied, linking the organizational strategies with the local and national contexts. By this way, an analysis of the strategies of enunciation and collective action of the peasants was built, highlighting the motivations and formative experiences, making it possible to highlight the role of resistance and organization of social categories that are often invisible.